CONFORMITY OF THE MODEL OF INFORMATION LEAKAGE SIGNALS FROM MONITOR SCREENS ON RARE CRYSTAL STRUCTURES WITH EXISTING SIDE ELECTROMAGNETIC RADIATIONS - Yevgrafov, Dmutro; Yaremchuk, Yurii (Ukrainian Information Security Research Journal, 2022)
For the previously obtained temporary model of information leakage from monitors based on crystal structures, it is important to confirm the results in practice. The composition of the equipment for studying the spectra of information leakage signals at frequencies from 46 to 84 MHz based on the Ezcap EZTV645-DVD-T Digital TV USB 2.0 Dongl SDR- receiver has been substantiated. It has been proven that there is no need to use radio-shielded rooms for research. In addition, it is shown how to calculate the spectrum of information leakage signals in the form of white-black stripes, horizontal and vertical blank impulses. The calculations are presented for signals from video cards of personal computer monitors in a simplified two-tone form of a static image, for an infinite analysis time. The creation of test images in the form of 54, 56, 58, 60, 62 white-black stripes and calculations of the spectra of information leakage signals for a monitor screen of 1024 by 768 pixels with a vertical frequency of 60 Hz and test images with 54, 58 and 62 white-black stripes. The scanning of the spectrum of signals of information leakage from the screens of monitors on the crystal structures and statistical processing of the results of measurements of the spectral characteristics of the signals is carried out. A conclusion is made about the consistency of the adopted signal model for further studies of spurious emissions from images on the monitor screen in the form of texts.